A review of 18O labelling Studies to probe the mechanism of aromatase (CYP191A). Issue 216 (February 2022) - Akhtar, Muhammad; Wright, J. Neville
Highlights: The aromatase reaction, converting androgens into estrogens, occurs in three steps, each requiring NADPH and O2 . In Step 1, a 19-hydroxy intermediate is produced, which in Step 2, is converted into a 19-oxo derivative presumably via a gem - diol intermediate with the stereospecific loss of HRe . In Step 3, a scission of the C-10-C-19 bond occurs releasing C-19 as formic acid (HCOOH) and incorporating an atom of oxygen from O2, The finding of Step3 has been questioned and the present paper deals with this issue. Abstract: Our previous studies, using precursors for two classes of estrogens, estrone and estriol, have highlighted the following facets of aromatase. The overall reaction, converting androgens into estrogens, occurs in three steps, each requiring NADPH and O2 . In Step 1, a 19-hydroxy intermediate is produced, which in Step 2, is converted into a 19-oxo derivative via a gem - diol intermediate with the stereospecific loss of HRe . In Step 3, a scission of the C-10-C-19 bond occurs releasing C-19 as formic acid (HCOOH) and incorporating an atom of oxygen from O2, The other oxygen atom of formic acid is derived from the hydroxyl group introduced in Step 1 . These experiments were performed using the classical placental microsomal system. Our findings were confirmed and extended by (the late) Caspi's group. However, incorporation of oxygen in Step 3, has been challenged in a subsequent study using a soluble reconstituted system. The latter authors have implied the superiority of their system over the microsomal preparation. However, several assumptions under pinning their own work were derived from the use of placental microsomes. Furthermore, the authors have not considered that when a previous work is challenged it needs to be repeated under the conditions described in the original publication.